Size-susceptibility of Cornu aspersum exposed to the malacopathogenic nematodes Phasmarhabditis hermaphrodita and P. californica. Issue 11 (2nd November 2021) - Grannell, Alex; Cutler, James; Rae, Robbie
ABSTRACT: Slugs and snails are agricultural pests usually controlled by chemical bait pellets however an alternative method is the commercially produced malacopathogenic nematode Phasmarhabditis hermaphrodita, which is sold across northern Europe. P. hermaphrodita can kill several slug species but is unable to affect larger pestiferous snails. Therefore, we examined whether the closely related species Phasmarhabditis californica, isolated from the U.K. could kill neonate or adult common garden snails ( Cornu aspersum ) . In our first experiment, neonate C. aspersum were exposed to 1000 nematodes per tube containing three strains of P. californica (designated DMG0017, DMG0018 or DMG0019) (as well as the commercial formulation of P. hermaphrodita DMG0001) and feeding inhibition and survival were monitored over 14 days. All nematodes apart from P. californica (DMG0017) killed the snails and caused feeding inhibition. In a follow up experiment we exposed adult C. aspersum to two doses (30 and 90 nematodes per cm 2 ) of P. californica (DMG0019) and P. hermaphrodita (DMG0001) and monitored survival, feeding inhibition and changes in weight over 21 days. Neither nematode species affected survival, feeding inhibition or weight of the adult snails. In summary, P. californica (DMG0018 and DMG0019) are as pathogenic as P. hermaphrodita (DMG0001) and could be used to target neonate snails, however, the use of malacopathogenic nematodes to control large adult snails continues to be problematic.